2015
DOI: 10.1016/j.exer.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Receptor mediated disruption of retinal pigment epithelium function in acute glycated-albumin exposure

Abstract: Diabetic macular edema (DME) is a major cause of visual impairment. Although DME is generally believed to be a microvascular disease, dysfunction of the retinal pigment epithelium (RPE) can also contribute to its development. Advanced glycation end-products (AGE) are thought to be one of the key factors involved in the pathogenesis of diabetes in the eye, and we have previously demonstrated a rapid breakdown of RPE function following glycated-albumin (Glyc-alb, a common AGE mimetic) administration in monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
4
19
0
Order By: Relevance
“…Specifically, the molecule exerts its inhibitory action by blocking the V domain of RAGE . Although this is a recently described RAGE inhibitor, several in vivo and in vitro studies have validated the binding specificity of FPS‐ZM1 with RAGE and the blocking of RAGE‐mediated downstream signaling cascades . The concentration of FPS‐ZM1 used in our experiments was also well within the effective and nontoxic levels as described in the literature .…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, the molecule exerts its inhibitory action by blocking the V domain of RAGE . Although this is a recently described RAGE inhibitor, several in vivo and in vitro studies have validated the binding specificity of FPS‐ZM1 with RAGE and the blocking of RAGE‐mediated downstream signaling cascades . The concentration of FPS‐ZM1 used in our experiments was also well within the effective and nontoxic levels as described in the literature .…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, these multiple factors may be influenced by sVEGFR-2 in DME, suggesting that anti-VEGFR therapy could be considered for macular edema in DME patients. This idea is supported by reports that VEGF-induced breakdown of the retinal pigment epithelium (RPE) barrier was blocked by pretreatment with relatively selective VEGFR-2 antagonists in both ARPE-19 and primary RPE cells [51] , and that the Glyc-alb-induced breakdown of RPE function was blocked by a relatively selective VEGFR-2 antagonist in both animal and tissue culture models [52] . This suggests that both anti-VEGF therapy and anti-VEGFR-2 therapy should be considered for DME.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly to other reports 7 12 our previous studies 13 , 14 have demonstrated that in experimentally induced type 1 diabetic (T1D) rats, several cell types of the retina, including astrocytes, Müller glia cells, photoreceptors, retinal pigment epithelium (RPE), amacrine and ganglion cells are already affected, even prior to significant apoptosis or clinically detectable vasculopathy.…”
Section: Introductionsupporting
confidence: 78%